The right to strike and its implementation in Ukraine - Слома, Валентина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This paper investigates the conditions and implementation of the right to strike by employees. Also the effects of the recognition of the strike illegal are described.